Guide to managing persistent upper gastrointestinal symptoms during and after treatment for cancer. Issue 4 (14th October 2016) - Andreyev, H Jervoise N; Muls, Ann C; Shaw, Clare; Jackson, Richard R; Gee, Caroline; Vyoral, Susan; Davies, Andrew R
Abstract : Background: Guidance : the practical management of the gastrointestinal symptoms of pelvic radiation disease was published in 2014 for a multidisciplinary audience. Following this, a companion guide to managing upper gastrointestinal (GI) consequences was developed. Aims: The development and peer review of an algorithm which could be accessible to all types of clinicians working with patients experiencing upper GI symptoms following cancer treatment. Methods: Experts who manage patients with upper GI symptoms were asked to review the guide, rating each section for agreement with the recommended measures and suggesting amendments if necessary. Specific comments were discussed and incorporated as appropriate, and this process was repeated for a second round of review. Results: 21 gastroenterologists, 11 upper GI surgeons, 9 specialist dietitians, 8 clinical nurse specialists, 5 clinical oncologists, 3 medical oncologists and 4 others participated in the review. Consensus (defined prospectively as 60% or more panellists selecting 'strongly agree' or 'agree') was reached for all of the original 31 sections in the guide, with a median of 90%. 85% of panellists agreed that the guide was acceptable for publication or acceptable with minor revisions. 56 of the original 61 panellists participated in round 2. 93% agreed it was acceptable for publication after the first revision. Further minor amendments were made in response to round 2. Conclusions: Feedback from the panel of experts developed the guide with improvement of occasional algorithmic steps, a more user-friendly layout, clearer time frames for referral to other teams and addition of procedures to the appendix.